1997
DOI: 10.1104/pp.115.2.773
|View full text |Cite
|
Sign up to set email alerts
|

Photoregulation of Chloroplast Gene Transcription in the Chromophytic Alga Heterosigma carterae

Abstract: Light acts as a complex regulator of cellular development and gene expression in photoautotrophs. Although light signals are highly effective in controlling cellular division and chloroplast biogenesis in the toxic marine alga Heterosigma carterae, their influence on gene expression has not been well characterized. To address this need cultures of H. carterae synchronized by an alternating light-dark regime were sampled through 12 h of light and 12 h of dark to characterize cell division, chloroplast complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…(RuBisCO), aldose-1-epimerase, and transketolase] and protein synthesis were up-regulated in apparent anticipation of the impending light phase (Fig. S6), in agreement with prior findings for genes encoding photosynthetic functions in algae (29)(30)(31)(32). This supports the theory that diatom gene regulation becomes entrained to anticipate the diurnal cycle such that the up-regulation of photosynthetic genes precedes the onset of light (33,34).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…(RuBisCO), aldose-1-epimerase, and transketolase] and protein synthesis were up-regulated in apparent anticipation of the impending light phase (Fig. S6), in agreement with prior findings for genes encoding photosynthetic functions in algae (29)(30)(31)(32). This supports the theory that diatom gene regulation becomes entrained to anticipate the diurnal cycle such that the up-regulation of photosynthetic genes precedes the onset of light (33,34).…”
Section: Resultssupporting
confidence: 81%
“…pseudonana appears to be broadly entrained to anticipate the diurnal cycle at the level of gene expression, as previously suggested (29,30). The shift from exponential growth to nutrientdepleted stationary phase attenuated many diel patterns of expression.…”
Section: Resultsmentioning
confidence: 57%
“…This is consistent with the phylogenetic result that HaAUREOs were divided to different groups. In addition, it is common that organisms up-regulate the expression of important genes in anticipation of changes in environmental cues (Doran and Cattolico, 1997). For example, many plants start to synthesize photosynthetic proteins before sunrise (Ashworth et al, 2013;Lin, 2002).…”
Section: Differential Transcriptional Responses Of Haaureo Genes To Lmentioning
confidence: 99%
“…In two raphidophytes H. akashiwo and Chattonella antiqua, Shikata et al (2015) observed that these species required (blue) light to regulate diurnal vertical migration (DVM), which plays an important role on HAB development and formation. Moreover, light signals are also highly effective in controlling cyst germination, cell survival and accumulation, and cellular division in H. akashiwo (Doran and Cattolico, 1997;Lee et al, 2012;Shikata et al, 2007). In other stramenopiles algae such as diatoms, xanthophytes, and phaeophytes, BL also promotes germination of resting cells, modifies their growth and behavior, and controls their cell division (Huysman et al, 2010;Ishikawa et al, 2012;Kataoka, 1990;Kropf, 1992;Mercado et al, 2004;Shikata et al, 2009Shikata et al, , 2015Takahashi et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…These organelles are surrounded by four membranes, indicative of their serial endosymbiotic origin from a putative rhodophytic ancestor [14,17]. As an obligate autotroph, H. akashiwo is dependent on chloroplast function for survival and responds to changing environmental cues by rapidly altering transcript levels within the plastid [18,19]. Run-on analysis clearly demonstrates that the changes in mRNA abundance are largely due to transcript initiation [19].…”
Section: Introductionmentioning
confidence: 99%